2019
DOI: 10.26906/znp.2019.53.1888
|View full text |Cite
|
Sign up to set email alerts
|

Strength Analysis of Glued-in Steel Rods With Different Locations in CLT Panels Cross Section

Abstract: New types of wood based building materials to which the CLT refers require an accurate evaluation of the strength of varioustypes of connections. CLT panels connections with glued-in steel rods are of interest due to the possibility of creating quickmounted and rigid joints in the factory. Since the CLT have the structure of the perpendicular orientated boards in adjacentlayers, the strength and behaviour of the pasted rods is difficult to predict. The purpose of this study was to establish thestrength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
0
0
4
Order By: Relevance
“… Ergebnisse von Bidakov et al [35] Experimental results reported by Bidakov et al [35] Quelle: Fraunhofer IFAM …”
Section: Untersuchungen An In Bsp Eingeklebten Stäbenunclassified
See 3 more Smart Citations
“… Ergebnisse von Bidakov et al [35] Experimental results reported by Bidakov et al [35] Quelle: Fraunhofer IFAM …”
Section: Untersuchungen An In Bsp Eingeklebten Stäbenunclassified
“…Die von Bidakov et al [35] beschriebenen Versuche wurden an nicht näher definiertem BSP durchgeführt. Alle Probekörper bestanden aus fünf ||‐⊥‐alternierenden Lagen mit je 30 mm Dicke.…”
Section: Untersuchungen An In Bsp Eingeklebten Stäbenunclassified
See 2 more Smart Citations